A survey on sports activity involvement, menstrual history and eating disorders in Malaysian female athletes - Yunan, Afiqah Khairunnisa (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
This study investigated sports activity involvement, menstrual history, and prevalence of eating disorders among Malaysian female athletes. A total of 50 female national and state levels athletes with mean age of 21.16 ± 2.31 years old participated in this study. They were 6 gymnasts, 17 swimmers, 5 cyclists, 7 long distance runners and 15 silat athletes. The participants were required to answer sports activity involvement questionnaire, menstrual history questionnaire, and Eating Disorder Examination Questionnaire (EDE-Q). Descriptive statistics was used to calculate frequency, mean, standard deviation and percentage. Independent t-test was performed to compare the measured variables between participants with regular and irregular menstruation. The present study found that 44 out of 50 of the total participants (88%) had regular menstruation, while 6 participants out of 50 of the total participants (12%) had irregular menstruation. The number of athletes who had irregular menstruation was 2 individuals in swimming and 1 individual in gymnastic, cycling, long distance running and silat respectively. In all the participants, the age at the beginning of training was 11.60 ± 3.61 years old. Meanwhile, the total training period was 7.96 ± 3.70 years. The total hour of training per week was 20.76 ± 14.44 hours/week. In the present study, the mean restraint that is one of the EDE-Q subscales of all the participants was 1.48 ± 0.25 (60 to 65 percentile rank) while the mean eating concern of all the participants was 1.15 ± 0.40 (75 to 80 percentile rank). The mean shape concern of all the participants was 2.22 ± 0.49 (55 to 60 percentile rank) and the mean weight concern of all the participants was 2.00 ± 0.52 (60 percentile rank). The global score of EDE-Q subscales was 1.71 (60 to 65 percentile rank) in all the participants. Comparisons of measured variables between participants with regular menstruation and irregular menstruation showed that age at the beginning of training was younger in participants with irregular menstruation (9.83 ± 4.07 years old) than participants with regular menstruation (11.84 ± 3.52 years old). The total training period in years was longer in participants with irregular menstruation (8.50 ± 3.33 years) than participants with regular menstruation (7.89 ± 3.77 years). The mean restraint of participants with irregular menstruation 1.93 ± 0.34 (70 to 75 percentile rank) was higher than participants with regular menstruation 1.42 ± 0.26 (60 to 65 percentile rank) and the mean eating concern participants with irregular menstruation 1.77 ± 0.99 (80 to 85 percentile rank) was also higher compared to participants with regular menstruation 1.06 ± 0.33 (75 to 80 percentile rank). The mean shape concern of participants with irregular menstruation 3.09 ± 1.02 (65 to 70 percentile rank) was greater than participants with regular menstruation 2.10 ± 0.46 (50 to 55 percentile rank) also the mean weight concern of participants with irregular menstruation 2.50 ± 0.80 (65 to 70 percentile rank) was higher than participants with regular menstruation 1.93 ± 0.51 (55 to 60 percentile rank). The global score of EDE-Q subscales was higher in participants with irregular menstruation (2.32; 75 to 80 percentile rank) than participants with regular menstruation (1.63; 60 to 65 percentile rank). Individual results of the information on measured variables of participants who had irregular menstruation showed that national level swimmer exhibited the highest global score of the global score of EDE-Q subscales, followed by national level gymnasts, state levels silat athlete, state level long distance runner, state level swimmer, and state level cyclist. The age of swimmers and gymnasts who started involving in training was young (7 to 9 years old) and the total training period in year was long (8-14 years). The total hour of training per week was high (12-16 hours/week) in swimmers and gymnasts. In conclusion, the present study results implying that participants with irregular menstruation seems to have high global score of EDE-Q subscales, i.e., restrain, eating concern, shape concern and weight concern. Irregular menstruation may be related to young starting age of the athletes involving in training and the long total training period in years.